Depresión y rendimiento académico en adolescentes del Colegio de Bachillerato 27 de Febrero - Durazno Yupangui, Juliana Fernanda (2024)
Depression is a mental disorder that affects the ability to cope with everyday life, it can occur at any age without exception, being the most vulnerable population adolescents, generating in them great impact on education as in the case of academic performance causing lack of concentration, little desire to perform school tasks, intellectual disability resulting in low grades. The objective of this research was to determine depression and academic performance in adolescents of the February 27 High School, period October 2022 - March 2023. Therefore, a quantitative, descriptive, crosssectional study was developed with the participation of 166 students between 15 and 18 years of age, to whom a data collection sheet was applied, the Beck depression test and their grades were requested from the educational institution. The following results were obtained: 12.05% of the adolescents aged 17 and 18 showed severe depression, 18.07% of whom were female; 40.96% of the adolescents aged 15 and 16 showed very good academic performance, 37.95% of whom were male; therefore, it was shown that there was no statistical significance between the two variables with a value of p=0.16. This shows that, although the students present a severe depression, they maintain a very good academic performance